2019
DOI: 10.1186/s13058-018-1089-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes during extended neoadjuvant letrozole treatment of breast cancer: distinguishing acquired resistance from dormant tumours

Abstract: BackgroundThe risk of recurrence for endocrine-treated breast cancer patients persists for many years or even decades following surgery and apparently successful adjuvant therapy. This period of dormancy and acquired resistance is inherently difficult to investigate; previous efforts have been limited to in-vitro or in-vivo approaches. In this study, sequential tumour samples from patients receiving extended neoadjuvant aromatase inhibitor therapy were characterised as a novel clinical model.MethodsConsecutive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 65 publications
5
21
0
1
Order By: Relevance
“…These processes turn into clinically overt relapses after some years [43]. This is in line with other research, which has found a positive correlation between tumor size and relapse [44], and also between tumor size and development of endocrine resistance [45]. A crucial question is, to what extent the preoperative carbohydrate load to the patients in the present study has promoted the EMT-process in the T2-T3 tumors and thus created more micro metastases [46,47].…”
Section: Discussionsupporting
confidence: 91%
“…These processes turn into clinically overt relapses after some years [43]. This is in line with other research, which has found a positive correlation between tumor size and relapse [44], and also between tumor size and development of endocrine resistance [45]. A crucial question is, to what extent the preoperative carbohydrate load to the patients in the present study has promoted the EMT-process in the T2-T3 tumors and thus created more micro metastases [46,47].…”
Section: Discussionsupporting
confidence: 91%
“…Tumors with high Ki67r are a very heterogeneous group in our study; however, our findings show that tumors with acquired resistance exhibit smaller changes in gene expression compared with sensitive tumors and that these tumor therefore more closely resemble their diagnostic samples, an observation in keeping with the study from Selli and colleagues (44). Taken together, this supports the notion that the presurgical exposure of ER þ tumors to AI markedly enhances the ability to reveal their dependence on classic ER signaling and therefore identify mechanisms of resistance.…”
Section: Discussionsupporting
confidence: 90%
“…These processes turn into clinically overt relapses after some years [43]. This is in line with other research, which has found a positive correlation between tumor size and relapse [44], and also between tumor size and development of endocrine resistance [45]. A crucial question is, to what extent the preoperative carbohydrate load to the patients in the present study has promoted the EMT-process in the T2-T3 tumors and thus created more micro metastases [46,47].…”
Section: Discussionsupporting
confidence: 88%